PERSEPSI KARYAWAN ATAS AUDIT MANAJEMEN SUMBER DAYA MANUSIA PADA KINERJA KARYAWAN - Putri Maharani, Luh Gede Dea; Ratna Sari, Maria M (E-Jurnal Akuntansi, 2014)
Human resources management audit objectives are: workforce planning, recruitment, selection, orientation and placement, training and development. This study aimed to examine the effect of the perception of employees for audits of human resources in the employee's performance of The Haven Hotel Seminyak. The population in this study were all employees who work at The Haven Seminyak Bali. Obtained a total of 36 employees were selected as sample with purposive sampling. Data collection method used was a questionnaire. This study used a descriptive statistical analysis, the data intervalisasi, test the research instrument, the classical assumption and hypothesis testing using multiple linear regression analysis. The results showed that workforce planning, recruitment and selection of positive influence on employee performance, while the orientation and placement, as well as training and development does not affect the performance of employees.
Keywords: employee performance, planning, recruitment, selection,orientation